Global, regional, and national under-5 mortality, adult mortality, age-specific mortality, and life expectancy, 1970–2016: a systematic analysis for the Global Burden of Disease Study 2016 - GBD 2016 Mortality Collaborators (2017)
Submitted by Paula Saraiva (psaraiva@egasmoniz.edu.pt) on 2017-11-21T16:35:28Z No. of bitstreams: 1 Artigo15_NTaveira.pdf: 8147321 bytes, checksum: f2e3eb3da5fc66a5d73057c4a6a0f3b0 (MD5)